Assessing climate change impacts on meteorological drought indices for agricultural areas in Chi River Basin, Thailand: Comparative analysis of standardized precipitation index and standardized precipitation evapotranspiration index - Promping, Thanasit; Foyhirun, Chutipat; Tingsanchali, Tawatchai (Agriculture and Natural Resources, 2025)
Importance of the work: Meteorological drought indices play a critical role in understanding the impact of climate change on water resources. Objectives: To assess meteorological drought indices under future climate change impact in the Chi River Basin, a drought-prone region in northeast Thailand. Materials and Methods: The responses to projected climate changes were elucidated for the widely used standardized precipitation index (SPI) and standardized precipitation evapotranspiration index (SPEI). Projections indicated shifts in rainfall and temperature based on three regional climate models (ACCESS, CNRM and MPI) under two commonly used climate change representative concentration pathways (RCP4.5 and RCP8.5). Results: Analysis of the SPI and SPEI values derived from computed monthly data for 1 mth, 3 mth and 6 mth drought intervals indicated a temporal shift in drought conditions. Specifically, SPI exhibited a dry-to-wet-to-dry pattern across the 2020s, 2050s, and 2080s, while SPEI showed a persistent wet condition in the 2020s and 2050s, followed by a shift to dry conditions in the 2080s. Strong positive correlations (Pearson’s correlation coefficient = 0.86–0.97) between SPI and SPEI were observed from the 1990s to the 2080s. The SPI signaled potential drought events across all agricultural areas, while the SPEI indicated unaffected or wet conditions. However, the SPEI had a slower response to changes in drought conditions compared to the SPI. Model performance for both the SPI and SPEI showed unsatisfactory alignment with observed data under RCP4.5 and RCP8.5 during 2011−2020. Main finding: SPI and SPEI values can be used as components of a composite drought indicator, aligning with recommendations from the World Meteorological Organization and the Global Water Partnership in 2016 for a multi-indicator approach to provide a comprehensive representation of all drought types.